Kif kif : nieuwe stemmen uit Vlaanderen - Albdiouni, Naima; Amadou, Jamila; Boukhriss, Jamal (Antwerpen: Manteau; Amsterdam: Meulenhoff, 2006)
"Naima Albdiouni, Jamila Amadou, Jamal Boukhriss,... et al."